INVISIBLE CRIME: A CRIME THAT IS NOT DETECTED IN THE FORMAL LEGAL SYSTEM - Henny Saida Flora (PT. Anagata Sembagi Education, 2026)
This study examines the phenomenon of invisible crime, or crimes that go undetected in Indonesia's formal legal system. Crimes that are never reported, uninvestigated, or never reach the judicial process create a significant gap between real crime and officially recorded crime. This phenomenon is also known as the dark figure of crime, which is the difference between the number of crimes that actually occur and those recorded in official crime statistics. The study uses a normative-juridical method with conceptual, legislative, and comparative approaches. The results show that invisible crime is caused by various structural factors, including: weaknesses in the reporting system, social stigma against victims, complexity of evidence, limited capacity of law enforcement officers, and criminalization policies that are not adaptive to social developments. There are at least five main categories of invisible crime in Indonesia: sexual crimes and gender-based violence; corporate and white-collar crimes; cybercrimes; environmental crimes; and crimes within asymmetric power relations. This study recommends systemic reforms that include strengthening technology-based reporting mechanisms, expanding the definition of crimes and evidence in criminal procedure law, strengthening witness and victim protection, and a paradigm shift toward a victim-centered approach as a key pillar of effective law enforcement.